Five-fraction stereotactic radiotherapy for brain metastases: a retrospective analysis - Layer, Julian; Layer, Katharina; Sarria, Gustavo R.; Röhner, Fred; Dejonckheere, Cas S.; Friker, Lea L.; Zeyen, Thomas; Koch, David; Scafa, Davide; Leitzen, Christina; Köksal, Mümtaz; Schmeel, Frederic Carsten; et al. (Current oncology, 2023)
Purpose: To determine the safety and outcome profile of five-fraction stereotactic radiotherapy (FSRT) for brain metastases (BM), either as a definitive or adjuvant treatment. Methods: We assessed clinical data of patients receiving five fractions of 7 Gy each (cumulative physical dose of 35 Gy) to BM or surgical cavities. The primary endpoints were toxicity and radiation necrosis (RN) rates. Secondary endpoints were 1-year cumulative local control rate (LCR) and estimated overall survival (OS). Results: A total of 36 eligible patients receiving FSRT to a total of 49 targets were identified and included. The median follow up was 9 (1.1-56.2) months. The median age was 64.5 (34-92) years, the median ECOG score was 1, and the median Diagnostic-Specific Graded Prognostic Assessment (DS-GPA) score was 2. Treatment was well tolerated and there were no grade 3 adverse events or higher. The overall RN rate was 14.3% and the median time to RN was 12.9 (1.8-23.8) months. RN occurrence was associated with immunotherapy, young age (≤45 years), and large PTV. The cumulative 1-year local control rate was 83.1% and the estimated median local progression free-survival was 18.8 months. The estimated median overall survival was 11 (1.1-56.2) months and significantly superior in those patients presenting with RN. Conclusions: FSRT with 5 × 7 Gy represents a feasible, safe, and efficient fast track approach of intensified FSRT with acceptable LC and comparable RN rates for both the adjuvant and definitive RT settings.